PEMBELAJARAN TEKS BERITA PADA SISWA KELAS VII SMP NEGERI 11 SUNGAI RAYA TAHUN PELAJARAN 2023/2024 - Karimah, Nia Asmaul; Seli, Sesilia; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to see and describe the learning process starting from planning, implementation, to student learning outcomes on news text material in class VII of SMP Negeri 11 Sungai Raya in the 2023/2024 academic year. The method used in this research is descriptive with a qualitative research form. The data sources of this research are Indonesian language teachers, students of class VIIA, and teaching modules as documents related to news text learning. The research data were obtained from the results of Teacher Performance Assessment Tools 1 and 2, students' learning outcomes, and the results of interviews with Indonesian language teachers. Observation, interview, and documentation as techniques in data collection using observation sheets, note sheets, and documentation tools. Data validity testing used observation persistence and triangulation techniques. Data analysis used data reduction, data presentation, and conclusion drawing techniques. The data in this study are in the form of assessment results on learning planning, learning implementation, and student learning outcomes. The results of this study indicate that the assessment of learning planning is 83,1 with a good category, the assessment of learning implementation is 80,1 with a good category, while the ability to write news texts by students with an average score of 92,7 with a very good category.